O1-S02.04 Evidence of HPV vaccine effectiveness in reducing genital warts: an analysis of California Public Family Planning Administrative Claims Data, 2007–2009. (10th July 2011) - Bauer, H; Wright, G; Chow, J
Abstract : Background: The quadrivalent HPV vaccine, available in the US since 2006, is recommended for females age 9–26. This vaccine prevents HPV types 6 and 11, which cause 90% of genital warts (GW). Because of the rapid development of GW after infection, monitoring GW trends may provide early evidence of population level vaccine effectiveness. Methods: Trends in GW diagnoses were assessed using clinical encounter claims data from the California Family Planning Access Care and Treatment program which serves low-income females and males. Following implementation of diagnostic coding requirements, reliable data on International Classification of Diseases (ICD-9) codes were available 2007 through 2009. GW cases were defined as unduplicated clients with either an ICD-9 diagnostic code for viral warts (078.10) or condyloma (078.11) or a National Drug Code (NDC) for pharmacy-dispensed imiquimod or podofilox. Inclusion of procedure codes for destruction of genital lesions was unnecessary because these claims closely correlated (>95%) with appropriate ICD-9 codes. Denominators included unduplicated clients served. The proportions of clients with GW were stratified by age (<21, 21–25, 26–30, 31+), gender, and year. No data on vaccination status were available. Statistical significance of gender- and age-specific trends was assessed using the Cochran-Armitage test for linear trend. Results: Between 2007 and 2009, an average of over 1 735 000 female and 248 000 male clients were served annually. Total clients served increased each year for both females and males across all age groups, with the greatest increases seen among older age groups. Overall, 0.7% of females and 3.4% of males were diagnosed with GW. Between 2007 and 2009, GW diagnoses declined 19.4% among females less than age 21 (p trend <0.0001), whereas GW diagnoses were stable or increasing among females in older age groups see Abstract O1-S02.04 table 1 . No statistically significant declines in GW diagnoses were observed among males of any age group; however, significant increases were observed among older males. Conclusions: This analysis provides preliminary evidence that the HPV vaccine may be preventing GW among young women. Although using existing administrative claims data to assess trends in HPV-related diseases was inexpensive and expeditious, trends are ecological and may be explained by factors other than vaccination.